Revision Surgery of the Cleft Palate - Hu, Shirley; Levinson, Jared; Rousso, Joseph J. (Seminars in Plastic Surgery, 2020)
Cleft palate repairs often require secondary surgeries and/or revisions for a variety of reasons. The most common causes are symptomatic oronasal fistulas and velopharyngeal insufficiency. Complications from primary surgery, such as wound dehiscence, infection, and hematomas, contribute to the relatively high rate of revision surgery. Prevention of postoperative complications that may lead to fistula or velopharyngeal insufficiency is key, and many techniques have been described that have reportedly decreased the incidence of secondary surgery. Management varies depending on the nature of the fistulous defect and the type of velopharyngeal insufficiency. Numerous surgical options exist to fix this deficiency.
Keywords: cleft palate; revision cleft surgery; palatal fistulas; velopharyngeal insufficiency